Political psychology of voter preference: Candidate or Manifesto / Fairuz Hidayat Merican Wan Merican ... [et al.] - Wan Merican, Fairuz Hidayat Merican; Narani, Junaidi @ Saudi; Junaidi, Noni Harianti (Universiti Teknologi MARA, Cawangan Sarawak, 2009)
Candidate and manifesto are normally the two elements that are actively involved during an election especially the campaigning period. They are short-term factors and thus have an instant impact on voter preference within the election period itself. The objective of this study is to determine which of the two factors, between the candidate and manifesto, influences the voters’ preference the most when it comes to deciding who they will vote for. To find the answer a survey was taken among academic and non-academic staff of UiTM Sarawak. The questions were designed to gather information regarding the background of the staff as well as which of the two factors influences them the most. The questionnaire also gained feedback on the respondents’ preference based on the characteristics of the candidate and manifesto. Results of the study indicate that there seems to be no difference position-wise in terms of their choice between candidate and manifesto. Analysis also shows that in terms of the candidate, respondents are more influenced by the experience, education and residency of the candidate. As for the manifesto, respondents prefer issues related to education and economy. The scope and methodology of this study has the potential to be expanded and conducted on a wider and larger scale such as determining the preference of various electorates in our society such as the public-private sector voters as well as the rural-urban voters.